Saline-water irrigation and plant growth regulator application on zucchini fruit yield and quality - Souza, Maria W. de L.; Torres, Salvador B.; Oliveira, Francisco de A. de; Marques, Isabelly C. da S. [UNESP]; Pereira, Kleane T. O.; Guimaraes, Itala T. [UNESP] (Univ Federal Campina Grande, 2020)
The objective of this study was to evaluate the effect of a plant growth regulator (PGR; Stimulate') on the yield and quality of zucchini fruits from plants of the cultivar Caserta-Italiana grown under different salinity levels of the irrigation water (SLIW). A randomized block design was used, in a 2 x 6 factorial arrangement consisted of two SLIW (0.5 and 5.0 dS m(-1)) and six PGR application modes: imbibition of seeds for 8 h in distilled water (PGR-T1 ; Control); imbibition of seeds for 8 h in PGR at 10 mL L-1 (PGR-T2); imbibition of seeds for 8 h in PGR at 10 mL L-1 plus foliar application at 10 mL L-1 at the flowering stage (PGR-T3); imbibition of seeds for 8 h in PGR at 10 mL IP plus two foliar applications at the flowering stage and at 20 and 30 days after sowing (PGR-T4); foliar application at 10 mL L-1 at the flowering stage (PGR-T5); and two foliar applications at 10 mL L-1 at 20 and 30 days after sowing (PGR-T6). The SLIW affected differently the variables of the zucchini crops evaluated. The PGR application to plants under no salt stress (0.5 dS m(-1)) increased the solid soluble concentration and biomass accumulation of zucchini fruits. The PGR application as seed treatment and foliar application at the flowering stage increased the fruit yield of zucchini plants irrigated with saline water.
Keywords: Cucurbita pepo; Cucurbitaceae; abiotic stress; salinity